Investigation of the epithelial to mesenchymal transition markers S100A4, vimentin and Snail1 in gastroesophageal junction tumors. Issue 5 (19th October 2012) - Mirza, A.; Foster, L.; Valentine, H.; Welch, I.; West, C M.; Pritchard, S.
Summary Epithelial to mesenchymal transition (EMT) promotes tumor progression and invasion. As no study has focused on gastroesophageal junction (GEJ) tumors, the expression of three EMT‐related proteins (S100A4, vimentin, and Snail1) was investigated with the aim of assessing their pathologic and prognostic significance. Resection specimens were obtained from 104 patients who underwent surgery for GEJ adenocarcinoma, without preoperative chemotherapy. Three tissue cores were obtained from each of the tumor body (TB), luminal surface (LS), and invasive edge (IE) to produce tissue microarrays, and immunohistochemical staining was performed. The microarrays were scored independently by two observers. The demographic and histopathologic details of the patients were collected. Overall positive expression was observed in 88 (S100A4, 85%), 16 (vimentin, 14%), and 92 (Snail1, 89%) tumors. Staining for S100 A4 was positive in 79 (76%) of TB, 69 (66%) of IE, and 69 (66%) of LS specimens. Staining for vimentin was positive in 7 (6%) of TB, 11 (11%) of IE, and 5 (5%) of LS specimens. Staining for Snail1 was positive in 83 (80%) of TB, 51 (49%) of IE, and 78 (75%) of LS specimens. Positive staining of TB for S100A4 (P = 0.04) and Snail1 at IE (P = 0.01) was associated with involvement of circumferential resection margins. Positive staining for S100A4 in the TB (P = 0.02) and LS (P = 0.01) was associated with poor 5‐year overall survival. Vimentin had no statistically significant relationships with pathologic factors or outcome. The acquisition of mesenchymal protein S100A4 is associated with a poor prognosis in patients with GEJ tumors who undergo potentially curative surgery, and LS samples can be used to obtain prognostic information. Increased EMT‐related protein expression (S100A4, Snail1) is associated with the involvement of circumferential resection margin.